Notes on Early Land Plants Today. 60. Circumscription of Gymnomitriaceae (Marchantiophyta) - Vana, Jiri; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2014)
Gymnomitriaceae Klinggräff (1858: 16) was thoroughly treated by Váňa et al. (2010). Since the publication, a series of papers have shown that the circumscription of the family and genera within the family must be revised.